SYNTHESIS AND CHARACTERIZATION OF SODIUM LIGNOSULFONATE FROM BAGASSE: THE EFFECTS OF CONCENTRATION AND SALINITY TOWARD THE PERFORMANCE OF OIL INJECTION IN CORE - SETIATI (NIM : 32212006), RINI
Surfactant injection is one of the types of chemical injections used in Enhanced Oil Recovery (EOR) process. Surfactant has the capability to increase the interfacial tension between oil and water in the rock matrix, therefore the oil granules can be released and produced. The effectiveness of the surfactant in reducing the oil-water interfacial tension is affected by the type of surfactant used, the concentration of the surfactant and the salinity of the solution. The surfactant used in this study for the EOR is an anionic surfactant, which is one of the lignosulfonate surfactant derivatives. Currently, the commonly used surfactant is derived from petroleum lignosulfonate, however whenever the price of petroleum is high, then the price of surfactant would eventually rise.One of the lignosulfonate surfactants is sodium lignosulfonate surfactant (SLS surfactant) derived from lignin containing materials. One of raw materials having high content of lignin is bagasse, which contains lignin up to 24-25%. The processing of bagasse to produce lignosulfonate was initially performed by isolation of lignin from bagasse and the isolated lignin was subsequently transformed into sodium lignosulfonate by reaction between lignin and sodium bisulfite (NaHSO3). In this study, lignin has been successfully isolated from dried bagasse, which was confirmed through the analysis results of FTIR (Fourier Transform Infra Red) spectrum of isolated lignin that showed the same characteristic functional groups of lignin structure as the functional groups within lignin standard, which contains substituted phenolic aromatic groups and aliphatic alkene groups. Sodium lignosulfonate (SLS) surfactant having the same characteristics functional groups as the functional groups within the sodium lignosulfonate standard, which comprises the absorption peaks corresponing with the stretching vibration of aromatic and aliphatic alkene functional groups, the stretching vibration of sulfonate groups, and the bending vibration of carboxylic groups. The analysis of NMR (Nuclear Magnetic Resonance) spectroscopy of SLS surfactant showed that the surfactant consisted of monomer structure having methoxyl and hydroxyl substituted benzene,as well as the presence of sulfonate and aliphatic hydroxyl groups. Therefore, according to NMR spectrum analysis, it can be deduced that the monomer of synthesized surfactant has empirical formula of (C11H16O8S)n with relative molecular weight of 308.06. The exact molecular weight of the synthesized surfactant should be further determined using mass spectrometry measurement. The monomer of the synthesized SLS has a HLB (Hydrophilic-Lipophilic Balance) value of 11.6 which can be classified as O/W (Oil in Water) emulsion, which means that the SLS surfactant is water soluble. Thus, the SLS surfactant derived from bagasse can be used as an injection fluid and formed middle-phase emulsion that required in surfactant injection performance. According to the characteristic tests, the bagasse's SLS surfactant has some qualified characteristics which has a good aquoeus stability, clear solution and does not cause turbidity, capable to form middle phase microemulsion with light oil, while incapable to form middle phase emulsion with medium and heavy oil. Furthermore, based on the IFT tests, it showed that the salinity and surfactant concentrations influence the IFT values. The greater the surfactant concentration, the smaller the IFT value until a certain minimal value of IFT achieved, namely the critical micelle concentration (CMC). Similarly, the higher the salt content of the surfactant solution, the smaller the IFT value until reaching the CMC value. At higher salinity conditions, the IFT values become larger. This condition occurs due to the concentration of a particular salt, which showed that the presence of NaCl will cause a decrease in interfacial tension between oil – water, therefore the O/W emulsion formation would be ineffective. Consequently, when a surfactant injection operation contains a salt of NaCl, HCl and RSO3Na were formed, which would decrease the oil-water interface tension. In this research, the surfactant composition of 4.5% of SLS surfactant in- 80,000 ppm NaCl gave the lowest IFT value of 1.091 mN/m. Furthermore, the surfactant with the optimum composition has been tested toward its static and dynamic adsorptions. At the same surfactant concentration in different salt content, it showed that the higher the salt content, the lower the adsorption value, which means that the surfactant is less absorbed into the rock when the surfactant was injected to the core. Since the less surfactant was absorbed into the core, it means that more surfactants were available and capable to decrease the interfacial tension between oil – water,therefore the more oil can be produced by the surfactant injection. Wettability test results also showed that the higher salt content produces a larger contact angle which means the system becomes more water wet. These conditions has made the synthesized SLS surfactant derived from bagasse more dissolved in formationwater to release oil beads attached to the core.In the injection process, the composition of surfactant – salinity = 1.5% - 80,000 ppm showed the highest oil recovery valueup to 10.71%, compared to the other composition. Therefore,the surfactant concentration and salinity affected many factors related to the performance of SLS surfactant of bagasse displacement on light oil/petroleum. The results of this study has confirmed the hypothesis that bagasse can be processed into sodium lignosulfonate (SLS) surfactant having certain characteristics corresponded to the required characterisctics having good compatibility with light oil in relatively high salinity. The results of this study showed that the synthesized SLS surfactant of bagasse with its natural characteristics can be used as injection fluid in surfactant injection to increase oil recovery, especially for the light oil recovery.